Foraging habitat selection of overwintering Black-necked Cranes in the farming area surrounding the Caohai Wetland, Guizhou Province, China - Dawei Wu; Canshi Hu; Mingming Zhang; Zhumei Li; Haijun Su (Avian Research, 2020)
Abstract Background Understanding how overwintering birds choose foraging habitats is very important for conservation management. The overwintering Black-necked Crane (Grus nigricollis) feeds on crop remains in farmlands; thus, reasonable conservation management of this type of farmland that surrounds wetlands is critical for the overwintering populations of the Black-necked Crane; however, it is not clear how the Black-necked Crane chooses the foraging land in the farmland. Methods A thorough field positioning survey of all foraging sites in farmland areas around the Caohai Wetland and a sampling analysis of habitat selection by the Black-necked Crane were conducted during the winters from 2016‒2017 and 2017‒2018. Results Multiple factors contributed to the selection of foraging habitat in farmlands, i.e., food factors (crop remains and tillage methods) > human disturbance factors (distance to road and settlement) > topography factors (slope aspect), listed according to the strength of influence. Additionally, Black-necked Cranes tend to choose farmland sites where there was no machine tillage, the crop remains were > 500 g/m2, the distance to residences ranged from 100 to 500 m, the distance to roads ranged from 50 to 100 m, and the slopes exhibited western or eastern aspects. As the winters progressed, the volume of the edible crop remains declined, and the influences of the other main factors also changed, i.e., the factors of human disturbance (distance to road and settlement) became less important, while the effect of the food factor (crop remains) was strengthened. Thus, the foraging sites near the road became more important. Conclusion The farming area surrounding the Caohai Wetland is very important for the overwintering Black-necked Crane. Food factors and human disturbance factors are the main factors that influence the choice of feeding ground.